Analysis of the Surface Friction and Wear Properties of High Temperature γ-TiAl Alloy in Ultrasonic-Assisted Milling - Wei, Chenyang; Wang, Guangmiao; Xiang, Yunfei; Gao, Guofu (International Journal of Mechanical and Electrical Engineering, 2025)
γ-TiAl alloy, with its excellent creep resistance, oxidation resistance, and corrosion resistance, is regarded as one of the most promising materials in high - end fields such as aerospace. In aerospace and other fields, the requirements for the surface friction and wear performance of components are extremely stringent. However, the surface properties after traditional processing have limitations. Therefore, it is of great significance to seek more excellent processing methods to improve the friction and wear characteristics of the material. In this paper, ultrasonic - assisted high - temperature milling was carried out on the γ-TiAl cladding layer prepared by the laser directed energy deposition technology and the γ-TiAl castings, and the friction and wear performance of the machined surfaces was analyzed. The experimental results indicate that, compared with castings, the cladding layer has better surface wear resistance due to its smaller internal structure size. In comparison with the surface of the cladding layer processed by conventional machining, the friction coefficient and wear cross-sectional area of the surface processed by ultrasonic machining are reduced by 4.1% and 57.27% respectively, demonstrating that the surface processed by ultrasonic - assisted machining exhibits more excellent friction and wear performance.